PELATIHAN PENGEMBANGAN KETERAMPILAN GURU DALAM MENINGKATKAN EFEKTIVITAS PENILAIAN MELALUI MEDIA QUIZIZZ DI MA AL-FAKHRIYYAH DAN MA RAUDHLATUL MUTAÁLLIMIN PACET KABUPATEN BANDUNG - Sukma Cipta, Eliva; Matusaadah, Ali; Nursaidah, Cici; Mardwi Reksa, Dregi Okta; Faujiah, Lillah; Masrofah, Listia Wangi; Putri, Silmi Nur Azmi; Arisanti, Siti Anisa (Jurnal Abdimas Bina Bangsa, 2024)
The development of digital technology has had a significant impact on the world of education. Various digital tools and applications are now available to support the learning process, one of which is interactive media that makes it easier for teachers to manage classes and assess students. The use of technology in education, such as online assessment applications, is very helpful in increasing student engagement and making it easier for teachers to provide feedback quickly and effectively. One of the applications that is widely used in the learning process is Quizizz. The purpose of this training is to improve teachers' skills in using Quizizz media as an effective evaluation tool in MA Al-Fakhriyyah and MA Raudhlatul Mutaállimin Pacet Bandung. The implementation method consists of preparation, implementation and mentoring. The results of the training on the use of Quizizz show that this method is very attractive to the teachers of the trainees. They found the training to be very rewarding and enjoyable, while also improving their tech skills. In addition, it allows teachers to compose interactive quizzes with multimedia integration such as videos and images, which can make the learning atmosphere more dynamic. The use of this technology also supports more adaptive and flexible teaching, so that it can be applied in various subjects, providing a more meaningful learning experience for students